The Global Technology Revolution China, In-Depth Analyses Emerging Technology Opportunities for the Tianjin Binhai New Area (TBNA) and the Tianjin Economic-Technological Development Area (TEDA) - Silberglitt, Richard (RAND Corporation, 2009)
China's Tianjin Binhai New Area and the Tianjin Economic-Technological Development Area commissioned a technology-foresight study to help them plan for economic growth. The authors recommend seven emerging technology applications (TAs)--solar energy, mobile communications, rapid bioassays, new water-purification systems, molecular-scale drugs, electric and hybrid vehicles, and green manufacturing--and describe drivers, barriers, and plans for each.